Акустоелектричні канали витоку інформації - Павленко, Я. С. (ХНУРЕ, 2023)
Acoustoelectric transducers are widely used in various applications, including data communication, sensing, and imaging systems. Acoustoelectric transducers convert electrical signals to acoustic waves and vice versa, making them vulnerable to technical channels of information leakage. Countermeasures to prevent information leakage through acoustoelectric transducers include physical isolation, shielding, and filtering techniques. A comprehensive understanding of the technical channels of information leakage in acoustoelectric transducers is crucial for the design and implementation of secure systems.
Keywords: акустоелектричні канали; виток інформації